Utilization of Lactobacillus SP as prophylactic treatment againstMDR Staphylococcus aureus associated with burn wound infection - Tabark Hassn Mohammed kazm; Zainab Ziad Ramadan Hassan; Duha obaid Hameed jasim; Fatima Nawfel Ali Rida; Maryam Mohammed Abd Jassam (Genius Journals, 2024)
Infection remains the most common complication after burn injury and can result in sepsis and death, despite the use of topical and systemic antibiotics. Staphylococcus aureus is a frequently implicated pathogen. This study will evaluate the ability of the probiotic organism Lactobacillus sp. to inhibit the pathogenic activity of Pseudomonas aeruginosa, both in vitro and in vivo sothat it can be used as prophylactic treatment to prevent the infection. Using probiotics directly to burn wounds is an attractive novel intervention that avoids the pitfalls of standard antibiotic therapies.
Keywords: wound infection; Staphylococcus aureus; Lactobacillus